Effect of Density on Water Content of Making Corn Skin and Cob Biocharcoal Briquettes - Hafiza, Hafiza Nur; Masthura, Masthura; Jumiati, Ety (BULETIN FISIKA; Vol 25 No 1 (2024): BULETIN FISIKA February EditionDO - 10.24843/BF.2024.V25.i01.p17, 2024)
Briquettes are a solid fuel substitute for fuel oil that is produced by burning agricultural waste that has been reduced to a small size or diameter, goes through a carbonization process, then molded under pressure with or without the addition of binders or other components. The aim of this research was to measure the density and water content of biocharcoal briquettes made from corn husks and cobs. This research was conducted using experimental techniques and quantitative methodology. Water content and density are the test variables used in the investigation. The research results showed that the best briquettes were obtained in sample D which had a density value of 0.584 g/cm 3 and a water content of 3.46%.